A new view of general purpose technologies - Uwe Cantner; Simone Vannuccini (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
The economic literature started to recognize the heterogeneity characterizing the nature of different technologies, introducing the concept of General Purpose Technologies. In this paper, we offer a new view of General Purpose Technologies, building on the historical as well as on the recent literature, enquiring more in deep the definitional problems related to the GPTs and the conditions for their emergence, together with the characteristic for their prevalence and pervasiveness. A Schumpeterian and evolutionary view pointing at the micro and meso level of analysis - that of the dynamics of firms and industries -, is in our view the privileged perspective economists need to adopt in order to revitalize the theoretical and empirical study of GPTs. The similarities with the emergence of dominant designs and the relations with dynamics of increasing returns and path dependency in the choice between alternative technologies offer us a set of tools well suited to study the establishment of GPTs as a process unfolding in time, more than as a single homogeneous shock.
Keywords: E32; L16; O30; O33; O40; 330; General Purpose; Technologies; Long Waves; Business Cycles; Dominant design; Pervasiveness of technologies; Neo-Schumpeterian economics; Technologiewahl; Lange Wellen; Konjunkturtheorie; Schumpeterismus